HUBUNGAN GAYA BELAJAR DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI KELAS X SMAN 2 SUNGAI TARAB KABUPATEN TANAH DATAR - Chania, Yen; Haviz, M.; Sasmita, Dewi (IAIN Batusangkar, 2016)
The purpose of this study was to determine whether there is a relationship of learning styles to student learning outcomes in learning biology. The strength of the relationship can be seen in the interpretation of the correlation table. This research is ex post facto with research subjects are students of class X SMAN 2 Sungaitarab the 2015/2016 academic year are 71 people with the sampling technique used was random sampling with an error rate of 5%. Data collection method for variable learning style is by questionnaire, while studying biology outcome variables using vocational school documentation data analysis technique used is the product moment correlation with the level of significance of the analysis results is set at 5%. The results showed that there are no significant and positive relationship between learning styles to student learning outcomes in learning biology, this is evidenced by rhitung (0.089) <rtabel (0, 235), the Ha Ho is rejected and accepted. Based on the results of the study showed no significant positive relationship between the three variables of learning styles to student learning outcomes in the subjects of biology, it is thus test this hypothesis does not support the research.Key words: learning styles, learning outcomes, biology